Developing Research and Literacy Based Madrasahs in Islamic Education: Strengthening Teachers’ Scholarly Publications for Professional Development - Fauzi, Imron; Hartono; Kholil, Mohammad (Journal of Islamic Education Research, 2023)
This study examines the development of research and literacy based madrasahs as a strategy for strengthening teachers’ scholarly publication practices and professional development within Islamic education. Employing a mixed methods design, the study was conducted at MTs Negeri 2 Jember and involved teachers participating in structured training on research methodology, academic literacy, and scholarly publication, followed by sustained mentoring. Quantitative data were collected through questionnaires measuring teachers’ research literacy and publication engagement, while qualitative data were obtained through interviews and document analysis of research outputs. The findings indicate that the integrated development of research literacy and academic literacy significantly enhanced teachers’ competence in designing research, writing academic manuscripts, and engaging in scholarly publication. Improved teacher capacity also had a positive impact on student research engagement, as reflected in the quality of student research proposals and achievement in national research competitions. Institutional support, particularly through the optimization of a madrasah based academic journal, played a crucial role in sustaining research culture and reducing barriers to publication. The study concludes that developing research and literacy based madrasahs offers a viable and contextually grounded model for enhancing teacher professionalism, strengthening research culture, and advancing the quality of Islamic education.